Putting the pension back in 401(k) retirement plans: Optimal versus default longevity income annuities - Vanya Horneff; Raimond Maurer; Olivia S. Mitchell (Goethe University Frankfurt, Center for Financial Studies (CFS), 2018)
A recent US Treasury regulation allowed deferred longevity income annuities to be included in pension plan menus as a default payout solution, yet little research has investigated whether more people should convert some of the 15 trillion they hold in employer-based defined contribution plans into lifelong income streams. We investigate this innovation using a calibrated lifecycle consumption and portfolio choice model embodying realistic institutional considerations. Our welfare analysis shows that defaulting a small portion of retirees' 401(k) assets (over a threshold) is an attractive way to enhance retirement security, enhancing welfare by up to 20% of retiree plan accruals.
urn:nbn:de:hebis:30:3-479692
Keywords: G11; G22; D14; D91; 330; life cycle saving; household finance; annuity; longevity risk; 401(k) plan; retirement